Penerapan Database Redis Sebagai Optimalisasi Pemrosesan Kueri Data Pengguna Aplikasi SIRESMA Berbasis Laravel: Implementation of the Redis Database as Optimization of User Data Query Processing for the Laravel-Based SIRESMA Application - Nur Ramadhan, Ilham; Saraswati, Galuh (Technomedia Journal, 2024)
This research evaluates the use of the Redis database in the Laravel-based Application, SIRESMA API endpoint, to overcome the problem of data query processing unresponsiveness. The test result shows that the implementation of Redis has significantly improved the access speed of most API endpoint reponses, with a total response time improvement of around 6.74%. However, it should be noted that there are certain endpoints that experience performance degradation, which indicates that the use of Redis should be tailored to the characteristics of the data and application usage to obtain optimal results. Meanwhile, future research can consider more detailed query diagnosis tools and other alternatives to improve application performance.